Thyroid sclerosing mucoepidermoid carcinoma with eosinophilia: a clinicopathologic and molecular analysis of a distinct entity - Shah, Akeesha A (Mod Pathol, 2016)
Sclerosing mucoepidermoid carcinoma with eosinophilia is a rare thyroid neoplasm of uncertain pathogenesis that resembles salivary gland mucoepidermoid carcinoma. This multi-institutional study characterizes the clinicopathologic and molecular features of this tumor by utilizing next-generation sequencing to assess common mutations and gene fusions involved in thyroid carcinogenesis as well as fluorescence in-situ hybridization for MAML2 translocations typical of salivary gland mucoepidermoid carcinoma. Nine cases (6 females and 3 males, mean age: 59 years, range 30–77 years) were identified. All cases were comprised of nests and strands of tumor cells with both squamous and mucinous differentiation embedded in a fibrohyaline stroma with an inflammatory infiltrate replete with eosinophils. All cases were p63 positive, thyroglobulin negative and showed variable expression of TTF-1. All nine cases were negative for MAML2 rearrangements. Five cases successfully tested by next-generation sequencing (ThyroSeq v.2 assay) were negative for mutations and translocations commonly involved in thyroid carcinogenesis. NTRK1 showed overexpression but no evidence of translocation. On follow-up, one patient died of persistent disease, whereas one of four remaining patients with available follow-up (mean: 7.3 years, range 4–11 years) demonstrated recurrence at 4 years. Thus, we show that sclerosing mucoepidermoid carcinoma with eosinophilia appears molecularly and morphologically distinct from follicular and C-cell-derived thyroid tumors as well as from salivary gland mucoepidermoid carcinoma. The overall and recurrence-free survival for these patients may be lower than for other well-differentiated thyroid cancers.